2017
DOI: 10.22159/ijpps.2017v9i9.19881
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Counselling on Knowledge, Attitude, and Practice of Hypertensive Patients in a Tertiary Care Hospital

Abstract: Objective: Hypertension is a leading cause of death and disability worldwide and proper assessment of knowledge, attitude, and practice (KAP) factors are helpful in its management. Our aim was to assess the knowledge, attitude, and practice among hypertensive patients and the impact of patient counselling on the same. Methods:A prospective study was conducted among hypertensive patients from November 2015 to April 2016. Suitably designed and validated KAP questionnaire was used to evaluate the baseline KAP sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
3
7
1
Order By: Relevance
“…No significant association was shown with tobacco and alcohol intake among modifiable risk factors. This is contradictory with other findings where tobacco use alcohol consumption has been found to be associated with hypertension [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 99%
“…No significant association was shown with tobacco and alcohol intake among modifiable risk factors. This is contradictory with other findings where tobacco use alcohol consumption has been found to be associated with hypertension [21][22][23][24].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to pharmaceutical care, the Brazilian Longitudinal Study of Aging (ELSI-Brazil) showed that BP control is associated with education level, socio-economic status, a private health plan, and obesity [27]. Thus, pharmacist intervention is important to provide education of patient and to improve medication adherence of hypertensive and heart failure patients [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…A similar treatment was given to our patient as well and she showed clinical improvement within the first 3 h of her presentation to the ED. The importance of providing patient education or counseling to hypertensive patients before their discharge from the hospital must be emphasized because it has been shown that compliance to drug therapy can be improved significantly, particularly when mediated by pharmacists [8][9][10].…”
Section: Case Reportmentioning
confidence: 99%